Synthesis and biological evaluation of 3-substituted 2-oxindole derivatives as new glycogen synthase kinase 3β inhibitors. Issue 9 (1st May 2019) - Lozinskaya, Natalia A.; Babkov, Denis A.; Zaryanova, Ekaterina V.; Bezsonova, Elena N.; Efremov, Alexander M.; Tsymlyakov, Michael D.; Anikina, Lada V.; Zakharyascheva, Olga Yu.; Borisov, Alexander V.; Perfilova, Valentina N.; Tyurenkov, Ivan N.; Proskurnina, Marina V.; et al.
Graphical abstract: Abstract: Glycogen synthase kinase 3β (GSK-3β) is a widely investigated molecular target for numerous diseases including Alzheimer's disease, cancer, and diabetes mellitus. Inhibition of GSK-3β activity has become an attractive approach for treatment of diabetes and cancer. We report the discovery of novel GSK-3β inhibitors of 3-arylidene-2-oxindole scaffold with promising activity. The most potent compound3a inhibits GSK-3β with IC50 4.19 nM. In a cell-based assay3a shows no significant leucocyte toxicity at 10 µM and is moderately cytotoxic against A549 cells. Compound3a demonstrated high antidiabetic efficacy in obese streptozotocin-treated rats improving glucose tolerance at a dose of 50 mg/kg body weight thus representing an interesting lead for further optimization.